(untitled) (Revista Internacional de Formação de Professores, 2018)
The debate about the teaching production process aims to present the analyzes of the determinations that constitute the educational activity. The discussion focuses on the problem of the genesis and development of a teaching practice that expresses the perspective of an education beyond capital. Thus, they present three objects of research: contributions studies in mathematics education for the formation of an emancipated society; relationships between the teaching activity of Mathematics and the formation of student individuality; process of emergence and development of teaching activity. These researches present contributions in the field of Mathematics Education and teacher training.